Manajemen Konflik Anak Orang Tua dalam Relasi Romantis Berbeda Agama - Ramadhani Putri Nasution, Anna; Budi Lestari, Sri (Interaksi Online, 2020)
Romantic relationships of different religions that are lived in the lives of young people in Indonesia are quite interesting because they are considered different from the habits of society in general. Romantic relations of different religions are prone to conflict. One of the many conflicts that will be faced is the views and blessings of parents who are certainly not easy to obtain because they are considered not in accordance with the values and norms that exist in religion and family. So someone who decides to undergo a romantic relationship of different religions is faced with the risk of conflict between themselves and their parents. The children and parents studied in this study were students who had or were undergoing romantic relations of different religions aged 19-21 years and one parent of the child using the in-depth interview method. This study aims to find out how the experience of children - parents in resolving conflicts based on romantic relations of different religions. Therefore, researchers use interpersonal conflict management theory as a reference to theoretical criteria. The data collection method of this study was in-depth interviews with three children who had or were undergoing romantic relations of different religions and one of their parents. The results of this study indicate that information about the romantic relations of different religious children is private information. Disclosure and closure regarding the romantic relations of different religions between children and parents is based on various kinds of motivations and different ways from one another. Dependency and conflicting goals trigger conflict between children and parents. Child and parent conflict management styles in this study are grouped into five categories, namely competition, avoidance, accommodation, compromise and collaboration. Based on the findings of research on interpersonal conflict management, researchers find that the conflict management style used in dealing with problems will depend on the individual itself, because each conflict management style has its own risks so it is a consideration of children and parents to decide conflict management will be used in the family so that it can reach the desired conflict resolution of children and parents